An Accuracy Study of Computer‐Planned Implant Placement in the Augmented Maxilla Using Mucosa‐Supported Surgical Templates. (2nd September 2014) - Verhamme, Luc M.; Meijer, Gert J.; Bergé, Stefaan J.; Soehardi, Rik A.; Xi, Tong; de Haan, Anton F.J.; Schutyser, Filip; Maal, Thomas J.J.
Abstract: Purpose: The purpose of this study was to determine the clinically relevant accuracy of implant placement in the augmented maxilla using computer planning and a mucosa‐supported surgical template. Materials and Methods: Twenty‐five consecutive edentulous patients with an extreme maxillar alveolar ridge resorption were treated with a bone augmentation procedure. In a second stage, six Brånemark MkIII Groovy (Nobel Biocare®, Zürich, Switzerland) implants were installed. Preoperatively, a cone beam computer tomography (CBCT) scan was acquired, followed by virtual implant planning and flapless implant placement using a surgical template. A postoperative CBCT scan was acquired and registered to the preoperative scan. The Implant Position Orthogonal Projection validation method was applied to measure implant deviations in both the buccolingual and mesio‐distal plane. The influence of fixation pins and the position on the dental arch were investigated with regard to implant deviations, and rotations and translations of the surgical template. Results: One hundred fifty implants were installed. In mesio‐distal direction, a mean implant deviation of 1.50 mm was scored at the implant tip, 1.27 mm at the shoulder, −0.60 mm in depth, as well as a mean deviation of angulation of 2.50°. In buccolingual direction, a mean implant deviation of 0.99 mm was found at the implant tip, 0.76 mm at the implant shoulder, −0.57 mm in depth, and a deviation of angulation of 2.48°. Of all implants, 53% was placed too superficial compared with the planning. The use of fixation pins and implant deviations in both buccal and mesial directions as also for rotations and translation of the surgical template showed statistically significant differences. Conclusions: Computer‐aided implant planning showed to be a clinically relevant tool. However, this study emphasizes that the surgeon should take into account that deviations are larger compared with implant placement without augmentation procedure. Deviations are mainly caused by angulations and translations of the surgical template.